Prevalence and trends of pelvic floor disorders in late pregnancy and after delivery in a cohort of Israeli women using the PFDI-20. (May 2016) - Yohay, David; Weintraub, Adi Y.; Mauer-Perry, Naama; Peri, Carmel; Kafri, Rachel; Yohay, Zehava; Bashiri, Asher
Abstract: Objective: To investigate the prevalence of pelvic floor disorders (PFD) in a cohort of Israeli women at late pregnancy and three months postpartum, to define changes in PFD rates and to evaluate various obstetrical factors that may correlate with these changes. Methods: A prospective longitudinal cohort study was conducted between March and July 2014. The PFDI-20 questionnaire (validated in the Hebrew language) was used to evaluate pelvic floor distress symptoms 24 h and 3 months after delivery (representing the third trimester and post-partum period, respectively). Patients with a preterm delivery (<36 completed weeks of gestation), delivery of a stillbirth, non-fluency in Hebrew and patients with inability to complete the questionnaire due to a communication problem were excluded from the study. In addition to the PFDI results demographic and clinical data were collected from the patients' medical records. Routine statistical methods were used to interpret the results. Results: During the study period 117 women answered the first questionnaire and only 37 had filled the second questionnaire. The most prevalent item group reported in the third trimester was the urinary distress symptoms. Urinary frequency was the most common with 65% of patients reporting this symptom. At the post-partum period the most prevalent item group reported was the colorectal and anal distress with 31.5% of patients reporting increased straining efforts. There was a mixed trend in the changes noted between the two questionnaires. While some items improved in the puerperium as compared with late pregnancy others have worsened. In a multivariable analysis the only statistically significant finding was that at the post-partum follow-up, stress urinary incontinence was significantly associated with spontaneous perineal tears at delivery. Other obstetrical parameters including episiotomy and birth weight were not found to be significantly associated with any of the PFD items. Conclusion: We have demonstrated that PFD is prevalent both in late pregnancy and in the puerperium. There are mixed trends of spontaneous recovery following childbirth. A significant association between perineal tears and SUI 3 months after delivery was noted.